A Phenomenological Approach to Understanding the Meaning and Characteristics of Primary Geography Teacher-Researcher Identities. Issue 4 (4th July 2021) - Lee, Dong-min
Abstract: This study aimed to interpret the meaning of primary geography teacher-researcher identities (PGTRIs) using phenomenology according to van Manen. Four emerging themes explained the meaning and characteristics of PGTRIs. The participating primary geography teacher-researchers (PGTRs) developed particular identities as practitioner agents of primary geography education research. Based on their aspirations for geography education research and their awareness of the problems in primary geography education, the PGTRs aimed to innovate in primary geography education and primary classroom-embedded geography education research and to connect primary classrooms with the academic world. The results provide an in-depth understanding of the meaning of research and education for PGTRs and their identities.